Islamic-Arab Morals, Virtues and Characters In Arabic-Tamil Novel “Madinatun Nuhas” Or “Tamirapattanam” - Zubair K M A, Ahamed; Nadwi, A. Abdul Hai Hasani; Al-Bukhari, M. Ahamedullah; Ali, M.Yasar Arafath; Ali, S.A. Usman (Ijaz Arabi Journal of Arabic Learning, 2024)
Tamirappattanam, also known as Madinatun Nuhas, is a unique piece of literature. It is the first Islamic novel written in India, penned in 1858 by Imam Al Aroos. This novel is unique in its content and script, utilizing the Islamic-Arwi or Arabic-Tamil script and the Dravidian-Tamil script. This research article conducts a comprehensive study of Tamirappattanam, examining its style, contents, and the author himself. It analyzes this novel, highlighting its uniqueness and role as a pioneering Islamic novel. This article aims to establish a position for Islamic novels and literature, tracing the initial endeavors in India. With its deep roots in the history of Islam, Islamic literature has always been a source of education and inspiration. This novel, Tamirappattanam, is a prime example. It weaves historical, legendary, and literary characters together in a narrative infused with Islamic themes and values. The novel explores the unique power and dominion of Prophet Sulaiman and the grandeur of the Abbasid Caliphate. It portrays Allah's bounty and supremacy while emphasizing the importance of Islamic morals and principles. The author skillfully combines art and literature to create a work that entertains and imparts Islamic teachings to the Ummah. Through the use of real historical figures and legends, the novel presents a vivid representation of Islamic culture and values. It balances sentiment and thought, offering a harmonious relationship between faith and moral values. Tamirappattanam is a significant contribution to Islamic literature, showcasing the artistic prowess of the author in crafting a narrative that educates and inspires readers. It serves as a powerful reminder of the enduring relevance of Islamic principles in shaping individual lives and society as a whole.